2015
DOI: 10.1016/j.apsusc.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Doping effect of In2O3 on structural and ethanol-sensing characteristics of ZnO nanotubes fabricated by electrospinning

Abstract: Indium-doped ZnO (IZO) nanotubes with various indium contents (0.01-0.20) were synthesized via a facile electrospinning method. Results of X-ray diffraction and transmission electron microscopy demonstrate that all samples are consisted of hexagonal wurtzite-typed ZnO, showing a well-crystallized indium-zinc-oxide solid solution when only a small amount of zinc ions substituted by indium ions (0.01). Once the amount of indium dopants ≥ 0.05, there will form some amorphous In 2 O 3 , leading to a pronounced dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 40 publications
(46 reference statements)
2
27
0
Order By: Relevance
“…The red shift in the absorption band edge of the heterostructure may be caused by the oxygen vacancies and defects due to the formation of the heterostructure. Similar results can also be observed in the previous studies reported by some researchers . This increment in the absorption band edge toward higher wavelength clearly predicts the application of In 2 O 3 ‐ZnO heterojunction toward visible range.…”
Section: Resultssupporting
confidence: 91%
“…The red shift in the absorption band edge of the heterostructure may be caused by the oxygen vacancies and defects due to the formation of the heterostructure. Similar results can also be observed in the previous studies reported by some researchers . This increment in the absorption band edge toward higher wavelength clearly predicts the application of In 2 O 3 ‐ZnO heterojunction toward visible range.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, many efforts have been devoted to the synthesis of ZnO nanostructures including quantum nanoparticles [20] nanorods [21], nanofibers [22], nanotubes [23], and three-dimensional (3D), hierarchical nanostructures [24]. However, most of them aimed at an investigation of the effects of morphology and crystal size on the sensing behavior but not on the exploration of their crystal plane-dependent properties.…”
Section: Zno Exposed Crystal Planes and Sensing Behaviormentioning
confidence: 99%
“…ZnO-based 1D nanostructured materials have been doped by Ce [11,193], Pr [6], Er [194], La [190,195], Pt [190], Cu [190,196], Mn [197], Co [198], Al [199], Pd [176] and In [200] and have been used to detect acetone, acetic acid, ethanol, H 2 S, and CO.…”
Section: Reviewmentioning
confidence: 99%